ANÁLISE DO PROCESSO DE ELABORAÇÃO DE PLANOS DE DESENVOLVIMENTO DE ASSENTAMENTOS RURAIS DO SEMIÁRIDO NORDESTINO - Roberto de Sousa Miranda (Universidade Federal do Maranhão, 2018)
The purpose of the paper is to analyze the process of elaboration of Develo- pment Plans of Settlements José Antonio Eufrosino and Osiel Pereira and the role of social institutions in the implementation of this policy. The research methodology was based on the literature review of visits, the follow-up mee- tings, in consultation with the book of minutes and carrying out semi-structured interviews with the settlers. The theoretical framework was neoinstitutiona- lism, which emphasizes the role of social institutions in the development of collective actions and the acquisition of common benefits. The formulation of the Settlement Development Plan is challenging because it requires a great mo- bilization of families to hold meetings to discuss: credit application, purchase of equipment for construction of houses, productive activities, technical assis- tance and basic infrastructure.